Cross metathesis-mediated synthesis of hydroxamic acid derivatives - Chattopadhyay, Shital Kumar; Ghosh, Subhankar; Sil, Suman (Beilstein Journal of Organic Chemistry, 2018)
An alternative synthesis of α,ß-unsaturated hydroxamates via cross metathesis between a class-I olefin and N-benzyloxyacrylamide is reported. The reaction proceeds better in the presence of Grubbs’ second generation catalyst within short time and in good yields (57–85%) with a range of substrates. Subsequent hydrogenation of each of the CM products delivers the title compounds in moderate to very good yield (70–89%). An important demonstration of the protocol is the preparation of the unusual amino acid component of the bioactive cyclic peptide Chap-31.
Keywords: α-amino acid; catalysis; cross metathesis; hydroxamates

Handbook of Metathesis - O'Leary, D. J.; O'Neil, G. W. (Cross-Metathesis, 2015)

Comprehensive Organic Synthesis - Zukowska, K.; Grela, K. (Elsevier, 2014)

(untitled) - Connon, S. J.; Blechert, S. (Angew. Chem., Int. Ed., 2003)

Olefin Metathesis-Theory and Practice - Zukowska, K.; Grela, K. (Cross Metathesis, 2014)

Handbook of Metathesis: Catalyst Development - Chatterjee, A. K. (Olefin Cross-Metathesis, 2003)

(untitled) - Montgomery, T. P.; Johns, A. M.; Grubbs, R. H. (Catalysts, 2017)

(untitled) - Ogba, O. M.; Warner, N. C.; O’ Leary, D. J.; Grubbs, R. H. (Chem. Soc. Rev., 2018)

(untitled) - Yu, E. C.; Johnson, B. M.; Townsend, E. M.; Schrock, R. R.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2016)
See for a recent reference.

(untitled) - Biermann, U.; Meier, M. A. R.; Butte, W.; Metzger, J. O. (Eur. J. Lipid Sci. Technol., 2011)

(untitled) - Bailey, G. A.; Fogg, D. E. (J. Am. Chem. Soc., 2015)

(untitled) - Ferrié, L.; Bouzbouz, S.; Cossy, J. (Org. Lett., 2009)

(untitled) - Choi, T.-L.; Chatterjee, A. K.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2001)

(untitled) - Guan, J.; Hachey, M.; Puri, L.; Howieson, V.; Saliba, K. J.; Auclair, K. (Beilstein J. Org. Chem., 2016)
See for a recent report of CM with N-alkylated acrylamides.

(untitled) - Boufroura, H.; Mauduit, M.; Drège, E.; Joseph, D. (J. Org. Chem., 2013)
See for CM with Weinreb’s amide.

(untitled) - Michrowska, A.; Bieniek, M.; Kim, M.; Klajn, R.; Grela, K. (Tetrahedron, 2003)

(untitled) - Demchuk, O. M.; Pietrusiewicz, K. M.; Michrowska, A.; Grela, K. (Org. Lett., 2003)

(untitled) - Malla, R. K.; Ridenour, J. N.; Spilling, C. D. (Beilstein J. Org. Chem., 2014)

(untitled) - Abbas, M.; Leitgeb, A.; Slugovc, C. (Synlett, 2013)

(untitled) - Bidange, J.; Fischmeister, C.; Bruneau, C.; Dubois, J.-L.; Couturier, J.-L. (Monatsh. Chem., 2015)
See for a detailed study of CM with acrylonitrile.

(untitled) - Bruneau, C.; Fischmeister, C.; Miao, X.; Malacea, R.; Dixneuf, P. H. (Eur. J. Lipid Sci. Technol., 2010)

(untitled) - Bilel, H.; Hamdi, N.; Zagrouba, F.; Fischmeister, C.; Bruneau, C. (RSC Adv., 2012)

(untitled) - Miao, X.; Malacea, R.; Fischmeister, C.; Bruneau, C.; Dixneuf, P. H. (Green Chem., 2011)

(untitled) - Mann, B. S.; Johnson, J. R.; Cohen, M. H.; Justice, R.; Pazdur, R. (Oncologist, 2007)

(untitled) - Yoshida, M.; Kijima, M.; Akita, M.; Beppu, T. (J. Biol. Chem., 1990)

(untitled) - Komatsu, Y.; Tomizaki, K.-Y.; Tsukamoto, M.; Kato, T.; Nishino, N.; Sato, S.; Yamori, T.; Tsuruo, T.; Furumai, R.; Yoshida, M.; Horinouchi, S.; Hayashi, H. (Cancer Res., 2001)

(untitled) - Mukherjee, J.; Sil, S.; Chattopadhyay, S. K. (Beilstein J. Org. Chem., 2015)

(untitled) - Mukherjee, J. P.; Sil, S.; Chattopadhyay, S. K. (Tetrahedron Lett., 2016)

(untitled) - Schmidt, B.; Pohler, M. (Org. Biomol. Chem., 2003)

(untitled) - Miao, X.; Fischmeister, C.; Bruneau, C.; Dixneuf, P. H.; Dubois, J.-L.; Couturier, J.-L. (ChemSusChem, 2012)

(untitled) - Skowerski, K.; Białecki, J.; Czarnocki, S. J.; Żukowska, K.; Grela, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Chattopadhyay, S. K.; Sil, S.; Mukherjee, J. P. (Beilstein J. Org. Chem., 2017)

(untitled) - Pahari, A. K.; Mukherjee, J. P.; Chattopadhyay, S. K. (Tetrahedron, 2014)